Quantification of high speed actions across a competitive microcycle in professional soccer - Miguel Angel Campos-Vazquez, Asier Zubillaga, Francisco Javier Toscano-Bendala, Adam Lee Owen, Alfonso Castillo-Rodríguez (Journal of Human Sport & Exercise, 2023)
The main aim of this study was to compare the high-speed training session (TRs) and competitive match (OMs) demands induced on professional soccer players across an in-season microcycle. Maximum velocity (MV) and the number of actions and distance performed at high (N-HV > 14.4 km·h-1), very high velocity (N-VHV > 19.8 km·h-1) and sprint (N-SP > 25.2 km·h-1), in different distance zones (0-5, 5-15, 15-30, >30 m) were evaluated. Twelve professional soccer players competing within the Spanish 1st Division were the participants of the study. TRs were categorised according to days leading to the match day (MD-5, MD-4, MD-3, MD-1). The results showed significant differences between OMs and TRs across all analysed variables, except for N-HV, N-VHV, and N-SP 15-30m in the comparisons between OMs and MD-4. In addition, N-SP 15-30 m in MD-4 and MD-3 were significantly higher than in MD-1 (ES = 0.87 and 0.80, respectively) without differences in MV highlighting a tapering strategy. To conclude, the current investigation revealed a potential tapering strategy in professional soccer in conjunction to highlighting a way of maintaining MV and high speed actions across low-distance ranges (<15 m). Therefore, it would be necessary to further induce task with high-velocity actions in high-distance ranges (>30 m) across the TRs in order to replicate the velocity peaks occurred in OMs.